A rare compound heterozygosity of hemoglobin Siriraj and β-thalassemia in a 72-year-old male: A case report (Indian Journal of Case Reports, 2026)
Microcytic hypochromic Anemia in elderly patients is commonly attributed to iron deficiency or chronic disease. However, hemoglobinopathies may remain undiagnosed until late adulthood. A 72-year-old male with no significant clinical symptoms, with a history of hypertension, diabetes mellitus (type 2), and peripheral neuropathy, came to our Center for blood glucose levels. High-performance liquid chromatography (HPLC) revealed an abnormal hemoglobin (Hb) pattern with an HbC fraction of 74.6% and an elevated HbA2 of 8.9%. Subsequent molecular analysis using Sanger sequencing identified compound heterozygosity for Hb Siriraj and β-thalassemia. This case highlights the importance of considering rare Hb variants and molecular testing in elderly patients with unexplained microcytic anemia. The coexistence of Hb Siriraj and β-thalassemia is rare in the Indian population.